Schedule-aware performance estimation of communication architecture for efficient design space exploration. - Sungchan Kim
In this paper, we are concerned about performance estimation of bus-based communication architectures assuming that task partitioning and scheduling on processing elements are already determined. Since communication overhead is dynamic and unpredictable due to bus contention, a simulation-based approach seems inevitable for accurate performance estimation. However, it is too time-consuming to be used for exploring the wide design space of bus architectures. We propose a static performance-estimation technique based on a queueing analysis assuming that the memory traces and the task schedule information are given. We use this static estimation technique as the first step in our design space exploration framework to prune the design space drastically before applying a simulation-based approach to the reduced design space. Experimental results show that the proposed technique is several orders of magnitude faster than a trace-driven simulation while keeping the estimation error within 10% consistently in various communication architecture configurations.
Keywords: Bus contention; Bus-based communication architectures; Communication overhead; Design space exploration; Processing elements; Queuing analysis; Schedule-aware performance estimation; Simulation-based approach; Static estimation technique; Task partitioning; Task scheduling